Feasibility and Effectiveness of a Higher Harmonic Control System for a Medium Utility Helicopter - Kim, D.-H.; Park, J.-S.; Bang, S.-W. (My University, 2023)
The application of a Higher Harmonic Control (HHC) system for vibration reduction on a medium utility heli-copter is under consideration. The HHC actuators are located between the main rotor actuator and the non-rotating swashplate. The higher harmonic variation of the blade pitch according to the N/rev higher harmonic motion of each HHC actuator is derived. The aeromechanical analysis model of the helicopter main rotor system is constructed using CAMRAD II, then the vibration responses with respect to the HHC actuator N/rev actuations are calculated to make a helicopter system model. Control authority of the HHC system to reduce vibratory hub loads is evaluated by closed-loop control simulations.
Keywords: Dynamics